Attitudes towards Research Methods in Education: Development of the ATRMQ Scale - Antonio Matas-Terrón; Lourdes Aranda; Pablo Daniel Franco-Caballero; Esther Mena-Rodríguez (MDPI AG, 2024)
The noticeable lack of knowledge among Spanish university students regarding the disciplinary content of research methodology is notable, despite the considerable potential benefits for curriculum design. This study represents the initial phase of a project aimed at analysing and ameliorating this deficiency. It sought to develop a scale to measure the attitudes of education students towards the content of research methods. The psychometric properties were analysed using an incidental sample of 447 students, of whom 87.9% were women and 12.1% were men, aged between 18 and 52 years. Of the total number of participants, 43.2% belonged to the Pedagogy Degree, 36.7% to the Early Childhood Education Degree, and 20.1% to the Social Education Degree of the Faculty of Educational Sciences of the University of Malaga. The instrument was developed based on the ATSQ scale by Ordoñez et al. Both exploratory and confirmatory factor analyses were conducted to assess its validity. The results demonstrate adequate psychometric properties and confirm a three-dimensional model. This model encompasses measures pertaining to three factors: two emotional (emotion− and emotion+) and one cognitive (estimated utility), facilitating the study of the students' attitude towards the subjects of research methods. Furthermore, it provides arguments to consider a second-order unidimensional model. This study concludes with a discussion on the concept of attitudes towards research methods. Additionally, it identifies future challenges in measuring this construct without linking it to teacher evaluation.